In vitro assessment of Brazilian red propolis against mycobacteria: antibacterial potency, synergy, inhibition of biofilm formation, and intramacrophage effects - Martins, S. B.; Teixeira, S. C.; de Souza, G.; Alhatlani, Bader Y.; Abdallah, Emad M.; Ambrosio, S. R.; Silva, T. S.; Bastos, J. K.; Tanimoto, M. H.; Barbosa, B. F.; Ferro, E. A. V.; Martins, C. H. G. (Frontiers in Pharmacology, 2025)
BackgroundTuberculosis persists as a major global health threat and remains the leading cause of death from infectious disease. Efforts to control the disease are increasingly hampered by the emergence of drug-resistant Mycobacterium tuberculosis strains. At the same time, non-tuberculous mycobacteria are an expanding clinical concern, with few effective therapies available. Brazilian red propolis (BRP) has shown broad-spectrum antibacterial activity, yet its efficacy against mycobacteria is poorly characterized.MethodsThis study evaluated the in vitro antimycobacterial potential of a crude hydroalcoholic extract of BRP (CHEBRP). Minimum inhibitory concentrations were determined against drug-susceptible and rifampicin-resistant M. tuberculosis strains (M. tuberculosis H37Rv–ATCC 27294, clinical isolate, and rifampicin-resistant clinical isolate; M. kansasii ATCC 12478 and clinical isolate; M. avium ATCC 25291 and clinical isolate). Fractional inhibitory concentration indices were calculated to assess interactions with isoniazid and rifampicin. Biofilm inhibition was measured, and cytotoxicity was assessed in RAW 264.7 macrophages. Intracellular activity was quantified using infected macrophage cultures.ResultsCHEBRP exhibited potent activity against most M. tuberculosis strains tested, including rifampicin-resistant strains. Its combination with isoniazid or rifampicin yielded an indifferent interaction, supporting the feasibility of co-administration. CHEBRP significantly inhibited biofilm formation, showed minimal cytotoxicity toward macrophages, and achieved substantial clearance of intracellular bacilli.ConclusionThese in vitro findings highlight CHEBRP as a promising candidate for adjunctive antimycobacterial therapy. Further studies should investigate its in vivo efficacy, pharmacokinetics, and activity against a broader range of mycobacterial species.